HUBUNGAN MUTU PELAYANAN KESEHATAN DENGAN TINGKAT KEPUASAN PASIEN RAWAT INAP DI PUSKESMAS HALMAHERA KOTA SEMARANG - Intan Zainafree; Shinta Ayu Respati (Dian Nuswantoro Semarang, 2016)
The quality of health services indicates healthcare perfection level in achieving patient’s satisfaction. Halmahera clinic applies health quality assurance system of ISO 9001:2008 with hospitalization as a flagship program. The indicator of hospitalization service of Halmahera clinic (BOR and LOS) in 2010-2013 was still below the standard and the satisfactory survey was not conducted regularly.The type of this research was an explanatory survey with cross sectional approach. The techniques used in taking the sample was a purposive sampling. The number of sample was 86.The results of this research showed that there was relation between the quality of health service dimension of reliability (0,008<0,05), dimension of assurance (0,043<0,05), tangible dimension (0,005<0,5), empathy dimension (0,005<0,05), responsiveness dimension (0,001<0,05) with patient’s satisfaction.The conclusion of this study was there was relationship between health service quality (reliability, assurance, tangible, empathy, and responsiveness) and the satisfaction of hospitalized patients of Halmahera clinic in 2014. Advice given to maintain the service quality of hospitalization of Halmahera clinic. Moreover, periodic survey of patient’s satisfaction should be conducted to maintain continuous improvement.Keywords: Health Service Quality, hospitalized patient, Patient Satisfaction